AB0715 Correlation of Clinical Symptoms and Instrumental Findings in as Coxitis. (15th July 2016) - Erdes, S.; Dubinina, T.; Rumyantseva, O.; Starkova, A.; Podryadnova, M.; Krasnenko, S.; Demina, A.; Urumova, M.; Agafonova, E.
Abstract : Background: Involvement of the hip joint (coxitis) is one of distinctive manifestations of ankylosing spondylitis (AS), resulting total hip arthroplasty in 5%>7% of cases. Objectives: To correlate the clinical features of coxitis in AS pts with radiographic and ultrasonographic findings. Methods: A total of 63 patients (mean age 31, 7±12, 7 years) with a diagnosis of AS (at the modified New York criteria 1984), having of pain in the hip joints, sequentially admitted for treatment at the clinic. Mean age of disease onset was 30, 8±9, 6 y. Hip pain was scored using VAS 100 mm. Coxitis was established on the basis of clinical symptoms - the presence of pain and/or limitation of motion in the hip joints at the time of admission of the patient to the clinic. Pelvic radiographs were taken in all pts to determine the severity of hip involvement using BASRI hip scale, and ultrasound examination was made using Sono Diagnost 360 (Philips) with linear (7, 5 MHz) and convex (5, 0 MHz) transducers. Joint effusion was set when the distance between the signals from the joint capsule and the inner part of the femoral neck was more than 7 mm. Results: Synovitis on ultrasonography found in 53 (81%) pts out of 61. Pts were grouped into 2 arms based on radiologic findings, i.e. Group with radiographic signs of coxitis and Group without radiographic abnormalities. Two groups comparison data are presented in the Table Conclusions: Ultrasound allows hip joint to clarify the cause of pain with similar clinical and radiographic manifestations, localized in this area, as well as to determine if the patient has synovitis in the early stages of the coxitis. Patients with radiological coxitis have a longer duration of the disease, severe functional disorders of the index BASFI, with the defeat of the peripheral joints is less common. Disclosure of Interest: None declared